2016
DOI: 10.1111/cxo.12442
|View full text |Cite
|
Sign up to set email alerts
|

Medical review licensing outcomes in drivers with visual field loss in Victoria, Australia

Abstract: Background Good vision is essential for safe driving and studies have associated visual impairment with an increased crash risk. Currently, there is little information about the medical review of drivers with visual field loss. This study examines the prevalence of visual field loss among drivers referred for medical review in one Australian jurisdiction and investigates factors associated with licence outcome in this group. Methods A random sample of 10,000 (31.25 per cent) medical review cases was extracte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Interestingly, a study of the scope of the problem of visual field loss among drivers in Australia highlighted that involvement of an expert medical advisory service in the state of Victoria resulted in increased likelihood that drivers with visual field loss would be allowed to continue driving. 7 Researchers continue to investigate the impact of visual field loss on driving and examine the evidence around the predictive ability of tests with the potential to assess for suitability to drive. A recent review highlighted the need for well-designed studies to examine the impact of visual impairment on driving outcomes and to better inform evidence-based policy around guidelines for fitness to drive.…”
Section: Key Pointsmentioning
confidence: 99%
“…Interestingly, a study of the scope of the problem of visual field loss among drivers in Australia highlighted that involvement of an expert medical advisory service in the state of Victoria resulted in increased likelihood that drivers with visual field loss would be allowed to continue driving. 7 Researchers continue to investigate the impact of visual field loss on driving and examine the evidence around the predictive ability of tests with the potential to assess for suitability to drive. A recent review highlighted the need for well-designed studies to examine the impact of visual impairment on driving outcomes and to better inform evidence-based policy around guidelines for fitness to drive.…”
Section: Key Pointsmentioning
confidence: 99%
“…However, visual acuity is the aspect of vision commonly measured during licensing. 4 WHO estimated that there are about 2.2 billion people with vision impairment or blindness globally, of whom about 1 billion have a vision impairment that could have been prevented or is yet to be addressed. 2 In Canada, cataract and visual pathway disease were the most common causes of visual impairment, both accounting for 40% of visual impairment with age-related macular degeneration and other retinal diseases as the next most common causes of vision loss.…”
Section: Introductionmentioning
confidence: 99%
“…5 Review of recent surveys on visual impairment in Latin America indicated that low vision occur more in rural Guatemala compared to Buenos Aires, and cataract was observed to be the main cause of low vision (41-87%), followed by posterior segment disease (7-47%) while in Australia, the occurrence of visual impairment in middle-aged people reported age-related macular degeneration, diabetic retinopathy, hemianopia or quadrantanopia and retinitis pigmentosa (RP) as conditions accounting for the majority of noncorrectable visual field loss. 4,6 Similarly, assessment of ocular status of commercial drivers in Osun, western part of Nigeria noted that eye diseases causing visual impairment and uncorrected refractive errors were seen to be common among commercial vehicle drivers. 7 Furthermore, road traffic accident was associated with visual impairment and field loss while RTA was less likely to occur among those who could read number plates (OR=0.51).…”
Section: Introductionmentioning
confidence: 99%
“…These reviews highlight the range of research undertaken in this area but underscore the urgent need for high quality research to support evidence‐based decisions about driving safety in those with visual impairment, particularly those with visual field loss. Research papers on the effects of simulated field loss on hazard perception and true visual field loss on vehicle control in a driving simulator demonstrate the complexity of the effects of field loss on driving‐related outcomes and highlight the problems in making licensing decisions for drivers with field loss as reported in another study . The potential for increased scanning behavioural training for older drivers to increase their scope of attention and improve safety at intersections, which pose a major problem for older drivers with and without visual impairment, is also explored …”
mentioning
confidence: 99%
“…Research papers on the effects of simulated field loss on hazard perception 4 and true visual field loss on vehicle control in a driving simulator 5 demonstrate the complexity of the effects of field loss on driving-related outcomes and highlight the problems in making licensing decisions for drivers with field loss as reported in another study. 6 The potential for increased scanning behavioural training for older drivers to increase their scope of attention and improve safety at intersections, which pose a major problem for older drivers with and without visual impairment, is also explored. 7 Other papers focus on the related issue of predicting whether drivers with visual impairment are safe to drive, an issue that is particularly relevant to policy makers charged with developing evidence-based guidelines that are fair to drivers with visual impairment, while maintaining the safety of our road systems.…”
mentioning
confidence: 99%